Engineering magnetism at functional oxides interfaces: manganites and beyond. (5th October 2017) - Yi, Di; Lu, Nianpeng; Chen, Xuegang; Shen, Shengchun; Yu, Pu
Abstract: The family of transition metal oxides (TMOs) is a large class of magnetic materials that has been intensively studied due to the rich physics involved as well as the promising potential applications in next generation electronic devices. In TMOs, the spin, charge, orbital and lattice are strongly coupled, and significant advances have been achieved to engineer the magnetism by different routes that manipulate these degrees of freedom. The family of manganites is a model system of strongly correlated magnetic TMOs. In this review, using manganites thin films and the heterostructures in conjunction with other TMOs as model systems, we review the recent progress of engineering magnetism in TMOs. We first discuss the role of the lattice that includes the epitaxial strain and the interface structural coupling. Then we look into the role of charge, focusing on the interface charge modulation. Having demonstrated the static effects, we continue to review the research on dynamical control of magnetism by electric field. Next, we review recent advances in heterostructures comprised of high T c cuprate superconductors and manganites. Following that, we discuss the emergent magnetic phenomena at interfaces between 3 d TMOs and 5 d TMOs with strong spin–orbit coupling. Finally, we provide our outlook for prospective future directions.